A Host-parasitoid Dynamics with Allee and Refuge effects (European Journal of Pure and Applied Mathematics, 2023)
We examine a discrete-time host–parasitoid model incorporating simultaneously an Allee and a refuge effect on the host. We investigate existence of a positive fixed point, local asymptotic stability, global stability of the fixed points and bifurcations. Numerical examples are given for verification of the theoretical results and we compare the model with existing data from the literature.
Keywords: Host-parasitoid, Nicholson-Bailey, Bifurcation, Allee effect, Refuge effect